Pilot Study: Reference & Research Support Services in Universiti Sains Malaysia Library, Year 2013 - Ahmat, Muhammad Akmal (Bahagian Rujukan dan Penyelidikan, 2013)
Reference & Research Division, USM Library has distributed an online survey to customers in Universiti Sains Malaysia starting March 2013. The main purpose of this pilot study was to investigate customer feedback on current and future demands for Reference & Research Services (RSS). There were 100 completed responses received. 89% were responded by students. The study found that the majority of respondents knew about RSS but they used the services ‘once in while’ (52%). When respondents got personal consultation from the staff, 79% of them felt that the staff were answered questions effectively. More over, 75% of them felt satisfied on overall reference services too. For Research Support Services expectation, the respondents felt that they are need to learn more about literature searching techniques (67%), academic writing skills (66%), and consultation on publishing academic articles (59%). Although more than 80% of respondents could not give ideas about the training courses for their needs, but 8% of them suggest RSS should run on publishing courses and 4% on statistical analysis software (SPSS) courses. 2